1993
DOI: 10.1056/nejm199312093292401
|View full text |Cite
|
Sign up to set email alerts
|

An Association between Air Pollution and Mortality in Six U.S. Cities

Abstract: Although the effects of other, unmeasured risk factors cannot be excluded with certainty, these results suggest that fine-particulate air pollution, or a more complex pollution mixture associated with fine particulate matter, contributes to excess mortality in certain U.S. cities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

72
3,973
18
102

Year Published

1994
1994
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 7,043 publications
(4,289 citation statements)
references
References 33 publications
72
3,973
18
102
Order By: Relevance
“…In a recent study examining ozone and asthma ED visits in New York City, a strong association was found for heavy smokers (defined as !13 pack years ), whereas none was found for light or never smokers (Cassino et al, 1999 ) . A somewhat higher risk of airpollution-related mortality was also observed in a longitudinal study in relation to tobacco smoke exposure (Dockery et al, 1993 ) .…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In a recent study examining ozone and asthma ED visits in New York City, a strong association was found for heavy smokers (defined as !13 pack years ), whereas none was found for light or never smokers (Cassino et al, 1999 ) . A somewhat higher risk of airpollution-related mortality was also observed in a longitudinal study in relation to tobacco smoke exposure (Dockery et al, 1993 ) .…”
Section: Discussionsupporting
confidence: 55%
“…The strong negative association between hydrogen ion and ED visits was surprising given that relatively high peak levels were observed, although results from epidemiologic studies of the effects of hydrogen ion have been mixed. Significant positive associations with various adverse health outcomes have been reported by some investigators (Burnett et al, 1997a;Delfino et al, 1997;Dockery et al, 1996a;Lippmann and Ito, 1995;Neas et al, 1995;Raizenne et al, 1996;Thurston et al, 1994 ), whereas in other studies, no effect was apparent (Dockery et al, 1996b;Schwartz et al, 1996) , or the effect of hydrogen ion was weaker than that of other measures of particulate matter (Dockery et al, 1993 ). This could be partially mediated by a very weak correlation between levels measured at centrally located monitors and personal exposure, which we have observed in Saint John (Stieb et al, 1998b) , and which has been reported elsewhere (Brauer et al, 1989;Suh et al, 1992 ).…”
Section: Discussionmentioning
confidence: 91%
“…Two recent cohort studies have suggested that long -term exposure to low levels of particulate matter (PM ) air pollution is associated with increased mortality due to, especially, respiratory and cardiovascular disease ( Dockery et al, 1993;Pope et al, 1995 ) . A more recent study has partly, but not completely, supported these findings ( Abbey et al, 1999 ) .…”
Section: Introductionmentioning
confidence: 99%
“…American Heart Association and the Environmental Protection Agency have officially acknowledged the detrimental effects of PM 2.5 on cardiovascular system and related morbidity outcome 2. The Harvard Six Cities study showed that the cardiopulmonary mortality was increased up to 37% in the population exposed to high levels of ambient PM 2.5 over a period of 14–16 years 22. The analysis from a population of 50 million living in the major U.S. cities (The National Morbidity, Mortality and Air Pollution Study) indicated that an increase of 10 μg/m 3 in PM 10 was related to an increase in 0.68% in cardiopulmonary mortality 23, 24, 25.…”
Section: Pm and Cardiovascular Diseasesmentioning
confidence: 99%